Ileal lymphangioma as a cause of intestinal obstruction in an adult patient: A rare case report (Indian Journal of Case Reports, 2025)
Most abdominal lymphangiomas are diagnosed at a very early age and are rarely found in adults. Abdominal lymphangioma is mainly found in the visceral organs, the retroperitoneum, the mesentery, or in the bones. In the gastrointestinal tract, they comprise <1% and are very rarely found in the ileum. Most of the time, gastrointestinal tract lymphangiomas are asymptomatic and are diagnosed incidentally. Symptomatic lymphangioma may present with a painless, palpable mass, colicky pain, and rarely with acute abdominal symptoms which leads to obstruction either due to volvulus or extrinsic mass effect which exerts traction on the bowel. A 38-year-old male case of ileal lymphangioma is described here which presented with lump and obstructive symptoms due to mass effect. Resection and anastomosis of the involved segment were performed with histopathology suggestive of submucosal cystic lymphangioma.